Quadruplex PCR for Phylogenetic Analysis of Uropathogenic Escherichia Coli in Iraqi Population - Kazaal, Meraim (Journal of Biomedicine and Biochemistry, 2023)
Background Escherichia coli (E. coli) are the most common cause of urinary tract infection (UTI). Clermont and his coworkers recently classi- fied E. coli strains into eight phylogenetic groups using a new quadruplex PCR method. This study aimed to identify the phylogenetic groups of E. coli based on Quadruplex PCR method to detect any of the phylogenetic groups that mainly cause UTIs in the Iraqi population.Method Isolates of Uropathogenic E. coli (UPEC) and other bacteria are identified by culture media and biochemical test, and then UPEC is subjected to phylogenetic analysis by a quadruplex PCR method.Results Out of 210 urine samples, only 114 (54%) samples have a pos- itive culture for E. coli with a count of 10 5 CFU/mL. The frequency of other bacteria are Enterobacter (24%), Proteus (10%), Pseudomonas (6%), Klebsiella (3%), Citrobacter (2%), and Acinetobacter (1%). In the present study, only seven groups of UPEC are detected and PCR profiles showed most UPEC isolate are related to B2 (42(36.8%)) followed by D (24(21.1%)), A 12((10.5%)), C(13(11.4%)), F (9(8%)), clade1 (8 (7%)), E (3(2.6%)) and unknown (3(2.6%)) but not detected any isolate below to group B1 (0(0%)). In the existing study, most phylogenetic groups were isolated from females and from patients in age groups 2, 3, and 4 (young and adults).Conclusion Only seven phylogenetic groups of UPEC are detected, in- cluding A, B2, C, D, E, F, and clade 1. Phylogenetic group B2 was the most common cause of UTI in the Iraqi population. Moreover, most UPEC phylogenetic groups are isolated from young and adult females.